A Field Trip to the Syn-Rift Petroleum System of Central Sumatera - Andrew Carnell; Chris Atkinson; Peter Butterworth (Ikatan Ahli Geologi Indonesia, 2013)
In September 2012, a field trip was run by the authors above into the Ombilin Basin of West Sumatra province to examine outcrop analogs of the syn-rift petroleum system of Central Sumatra. This was organized by SEAPEX and AAPG as part of the AAPG International Conference held in Singapore. The field trip started and finished in Padang but was conducted in the Barisan mountains amidst the stunning scenery of West Sumatra.Rift basin evolution is a key component of the petroleum systems of many Southeast Asian basins (e.g. South Sumatra Basin, Sunda Basin). Syn-rift lacustrine mudstones are prolific oil prone source rocks and syn-rift and early post-rift clastics sediments can provide excellent reservoir intervals. Rift petroleum systems are, however, geologically complex and hydrocarbon exploration within them requires a greater knowledge of the structures and sedimentological evolution of the basin than is often the case elsewhere. Local factors such as provenance and rift related tectonic activity can have a significant impact on the quality, quantity and distribution of source, reservoir and seal.The field trip was conducted over four days with each day concentrating on a separate aspect of the petroleum system as follows:Day 1 Basement and Regional Geology (SYN-RIFT)Day 2 Source Rock (SYN-RIFT)Day 3 Reservoirs (EARLY POST-RIFT)Day 4 Syn-rift Reservoirs (SYN-RIFT)